2022
DOI: 10.1186/s12936-022-04071-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Covid-19 on malaria services in three high endemic districts in Rwanda: a mixed-method study

Abstract: Background Rwanda has achieved impressive reductions in malaria morbidity and mortality over the past two decades. However, the disruption of essential services due to the current Covid-19 pandemic can lead to a reversal of these gains in malaria control unless targeted, evidence-based interventions are implemented to mitigate the impact of the pandemic. The extent to which malaria services have been disrupted has not been fully characterized. This study was conducted to assess the impact of Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…As another consequence of the COVID-19 pandemic, the provision of rapid diagnostic tests for malaria was fragile, which may have led to under-diagnosis of cases [ 42 ]. The main explanation for the lower number of malaria cases seen in health facilities was limited access to health facilities – public transportations were unavailable or unaffordable, and health facilities were closed or only provided reduced services [ 43 , 44 ]. This is supported by findings from a study from Rwanda which showed that health facility visits for malaria decreased while community health services for malaria increased [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As another consequence of the COVID-19 pandemic, the provision of rapid diagnostic tests for malaria was fragile, which may have led to under-diagnosis of cases [ 42 ]. The main explanation for the lower number of malaria cases seen in health facilities was limited access to health facilities – public transportations were unavailable or unaffordable, and health facilities were closed or only provided reduced services [ 43 , 44 ]. This is supported by findings from a study from Rwanda which showed that health facility visits for malaria decreased while community health services for malaria increased [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main explanation for the lower number of malaria cases seen in health facilities was limited access to health facilities – public transportations were unavailable or unaffordable, and health facilities were closed or only provided reduced services [ 43 , 44 ]. This is supported by findings from a study from Rwanda which showed that health facility visits for malaria decreased while community health services for malaria increased [ 43 ]. Finally, reports of hesitancy to visit health facilities due to fear of getting infected with COVID-19 were common [ 37 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Kwazulu Natal, South Africa, there was a 36% decline in clinic attendance and 50% decline in hospital admissions of children in April–June 2020, although the changes were less for the hospital births and testing of HIV-exposed infants. Although short-lived, there was a 47% increase in neonatal deaths in May 2020 [ 202 ]. In Rwanda, there was a reduction in malaria testing in health facilities among patients by 4.32 per 1000 population while testing in the community increased by 2.38 per 1000 population monthly, due to challenges and delays in accessing care at facilities [ 203 ].…”
Section: Impact Of the Covid-19 Pandemic On Essential Health And Othe...mentioning
confidence: 99%
“…Factors that may influence the likelihood of testing include symptom presentation, prevalence of the illness, availability of testing or treatment supplies, the ability of the health facility to manage COVID-19 as well as other common diseases, amongst others ( 9 , 10 ). A study in Rwanda found that there was a reduction in malaria testing at health facilities during the pandemic but increases in community-based testing ( 11 ). In contrast, a study in Uganda found that there was little impact on malaria testing early in the pandemic, but that there was a slight reduction in testing observed as the pandemic progressed ( 12 ).…”
Section: Introductionmentioning
confidence: 99%